First Faunistic Record of Alphitophagus bifasciatus (Say, 1823) (Coleoptera: Tenebrionidae) from East Anatolia (Turkey) - Özgen, İnanç (ABADER (Adıyaman Bilimsel Arastırmalar Dernegi), 2020)
With this study, brief information about the new distribution area and economic importance of the Alphitophagus bifasciatus (Say, 1823) (Coleoptera: Tenebrionidae) is given. It has been found in cereals, oilseeds, and in their products such as copra, cocoa, nuts, feed, dried fruit, herbs, and spices in previous years. It is possible in the following years that it will be characterized as potentially harmful by causing economic damage in the paddy fields in the Eastern and Southeastern Anatolia Regions of Turkey. Determining the specimen in this region is important in terms of faunistic and economic entomology in order to investigate the agricultural control management in the countries where it is pest related to the species and to reveal the plant protection strategy. © 2020, ABADER (Adıyaman Bilimsel Arastırmalar Dernegi). All rights reserved.
Alphitophagus bifasciatus (Say, 1823) (Coleoptera: Tenebrionidae)’un Doğu Anadolu Bölgesi’ndeki İlk Faunistik Kayıtı